Chemical Treatments to Reduce Off‐Flavor in Farm‐Raised Channel Catfish (Ictalurus punctatus) Fillet. Issue 3 (7th July 2016) - Liu, Shaoyang; Courtwright, Corey; Wang, Yifen; Hanson, Terrill R.
Abstract: The efficacy of chemical treatments on reducing musty off‐flavor in catfish fillets was evaluated in this work. Two ingredients, tea polyphenols and acetic acid, were found effective on removing the off‐flavor. Three treatments, i.e., 0.40 g/L tea polyphenols, 0.50% acetic acid and 0.40 g/L tea polyphenols + 0.50% acetic acid, presented significantly better results than water wash (the control). Mechanism study indicated that the three treatments were able to reduce the contents of geosmin and/or 2‐methylisoborneol which are the two major off‐flavor causing compounds in catfish fillet. The treatment with both of the ingredients showed slightly better results than the treatment with only one ingredient. Practical Applications: Off‐flavor is a major quality concern to farm‐raised catfish fillet. Major revenue lose could be caused by delay of harvest and/or defective products due to off‐flavor. This study offers a novel strategy to reduce the musty off‐flavor by chemical treatment, which could help the catfish industry improve fillet quality and lower production cost. The research indicated that tea polyphenols and/or acetic acid were effective to reduce/remove musty off‐flavor in farm‐raised catfish after harvest. The two chemicals could reduce the contents of geosmin (GSM) and/or 2‐methylisoborneol (MIB), which are the two major off‐flavor causing compounds in various fish fillets. Therefore, the treatments developed in this work may also be effective for other seafood products.